A review of topotecan in combination chemotherapy for advanced cervical cancer - Minoo Robati; David Holtz; Charles J Dunton (Dove Medical Press, 2008)
Minoo Robati, David Holtz, Charles J DuntonDepartment of Obstetrics and Gynecology, Main Line Gynecologic Oncology, Lankenau Hospital, Wynnewood, PA, USAAbstract: Treatment of advanced, recurrent or persistent cervical cancer includes radiotherapy and chemotherapy. Radiation has been the primary treatment modality for locoregionally advanced cervical cancer. Concomitant systemic cisplatin chemotherapy and radiation have shown high response rates with improvements in durable remissions and overall survival. Cisplatin has been the standard medication for the treatment of advanced cervical cancer. Combinations with other chemotherapeutic agents have been the subject of clinical trials with varying results. The toxicity of combination chemotherapy and tolerability of patients are other factors that should be considered in the management of patients with advanced disease. Recently topotecan, in combination with cisplatin, achieved increased response and overall survival rates without further compromising the patients’ quality of life. This review focuses on the mechanism of action and toxicities of topotecan, as well as its role as a radio-sensitizer and chemotherapeutic agent in the management of advanced, recurrent, or persistent cervical cancer. Other combination modalities and dosages are also discussed.Keywords: topotecan, combination chemotherapy, advanced cervical cancer